Decentralization Evaluation in Indonesia : The Dynamics of Relation Central Government and Local Government - Dewi Nurhalimah (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
Big bang decentralization in Indonesia has been started since 1999 as muffle of many problems after the fall of authoritarian regime in 1998. But no one can prove succeed rate, decentralization offered by World Bank is seen as an effective medicine to many countries different kind problems. Within the context, this paper evaluates the experiment of decentralization in Indonesia vigorous in revision by House of People’s Representatives, attention in 2004 Indonesia also apply recentralization and consequently a changed in the relationship central government and local government. Using institutional design analysis coupled with empirical observation. The final conclusion of this paper is sovereignty of the people controlled relation central government and local government.